Identifying performance differences among trail cameras used to monitor forest mammals - Kelsey Wellington; Christopher Bottom; Cody Merrill; John A. Litvaitis (Wildlife Society Bulletin)
ABSTRACT As a result of the increasing popularity of remotely triggered (trail) cameras among hunters, amateur naturalists, and field biologists, a large variety of equipment and technologies have become available. Among various models of cameras, such features as the size of detection zone, trigger speed, and sensitivity of infrared‐motion detector can influence performance, including animal detection rates. Variation in detection (or photographic) rates among cameras may be problematic in studies where several models of cameras are used, especially when performance differences are not incorporated in the study design. To evaluate this potential source of sampling bias, we conducted head‐to‐head field trials with 2 cameras (Cuddeback™ Capture IR and Reconyx™ HC 600 Hyperfire) that had substantially different attributes that can affect sampling efficiency. Among initial comparisons, we found that Reconyx cameras (large detection zone and high‐sensitivity motion detector) recorded approximately twice as many independent photographs as did the paired Cuddeback cameras. In subsequent trials, we reduced the sensitivity of the motion detector on the Reconyx cameras and positioned a wooden stake with bait in the center of the immediate detection zone of both cameras. These adjustments reduced performance differences between the 2 cameras. We recommend that biologists involved with research, inventory, or monitoring programs that rely on more than one model of trail camera consider a testing phase where they can evaluate and possibly adjust differences among cameras. © 2014 The Wildlife Society.